Factors Influencing the Choice of Place of Delivery among Women in Rural Northern Ghana: A Cross-sectional Descriptive Study - Gangtaba, Agulu Gilbert; Matsui, Mitsuaki; Kamiya, Yasuhiko (European Scientific Journal, ESJ, 2021)
Background of the Study: Studies have shown that three-quarters of all maternal deaths happen during childbirth and the immediate postpartum periods. Most of these deaths occur due to a lack of support from a health care provider. Globally, in 2016, one out of five childbirths took place without the assistance of a skilled birth attendant (SBA). The coverage among women in deprived areas is even lower. Women’s choice of a birthing place is often influenced by a complex mixture of factors ranging from individual, household, accessibility, health facility and provider-related factors, socioeconomic status, etc. Despite many interventions put in place in Ghana to encourage the use of health facilities for deliveries, utilization remains inadequate and the reasons have not been explored in detail. This study examines the factors affecting utilization of health facilities for delivery by pregnant women in the West Mamprusi Municipality (WMM) of Northern Ghana by adopting the three delays model. Materials and Methods: A crosssectional household survey of 381 women within the age group, 15-49 years, was conducted from January to March 2019 in the WMM. Data was collected using a structured questionnaire consisting of open and closed-ended questions. Data entry was done using IBM-SPSS version 25 statistical software, and it was exported to Stata version 15 statistical software for the analysis. Descriptive statistics and Chi-square tests were done. Bivariate and multivariate logistic regression analysis was conducted to identify the variables associated with facility delivery. All statistical tests were set at a 5% level of significance and a 95% confidence interval. Results: This study revealed that 75.3% of the respondents delivered their last child in a health facility while 24.7% delivered at home. The ANC coverage was high (98.2%). However, this does not translate into the proportion of facility deliveries. Factors leading to the choice of the delivery place include; poor health care provider’s attitudes, low knowledge about the signs of labor, poor quality of health services, sociocultural beliefs, low socioeconomic status of women, low educational level of mothers, and inaccessibility to health services. It was observed that respondents with a higher educational level were almost four times [AOR=3.66; 95% CI:1.19-68.9] more likely to deliver their children in a health facility. Women who made more ANC contacts with health care providers have a higher chance [AOR=1.17; 95% CI:1.04-36.7] of delivering in a health facility than those who made less or no contact. Conclusion: Though the findings show a high proportion of facility delivery in the study area, much can be achieved by intensifying health education on early initiation of ANC, signs of labor and delivery, as well as the importance of health facility delivery